ASSESSMENT OF SOCIO-ECONOMIC FACTORS AND CONSTRAINTS FACING COOPERATIVE TOMATO FARMERS IN IJEBU-NORTH LOCAL GOVERNMENT AREA OF OGUN-STATE, NIGERIA - O. Adebayo, M; C. Onugu, U; B. Jimoh, O (FUDMA JOURNAL OF SCIENCES, 2025)
The study assessed socio-economic factors affecting tomato production and challenges facing cooperative tomato farmers in Ijebu-North Local Government Area of Ogun-State, Nigeria. Data was gathered through a well-structured questionnaire administered to fifty (50) respondents using a two-stage sampling technique. Both descriptive and inferential statistics were absorbed to analyze collected data. The results showed that majority (90%) of farmers dominated by males involving in agricultural pursuits, with an average of 5 persons per households’ size along with a certain level of formal education. The results of constraints revealed that exorbitant high price of inputs (94%) ranked 1st, by inadequate storage facilities(90%) ranked 2nd, inadequate fund (86%) positioned 3rd among others emerged as predominant challenges adversely affecting tomato production. The F-statistic confirms appropriateness of the overall regression equation and significant at 1% level. The adjusted R², estimated at 0.78, showing that 78% of the variation explained in the models. Among the eigth(8) models regressed, five (5) were statistically significant, with four (4) variables displayed positive significant at1%,10%,5%,and1% levels respectively. Only one variable demonstrated negative significance at 5% significant level while three (3) of regressed variables displayed no significant. Therefore, the study recommended that farmer should be encouraged and educated by extension agents through effective and efficient passing of useful information to farmers. Agricultural loan facilities should be made easily accessible to the farmers to ensure timely and adequate procurement of tomato production inputs.Tomato farmers should form themselves into cooperative groups and also pool their resources together for easy access of farm inputs.